From advertising to consumer culture studies: The long and productive process of creating a shared theory - Hellín, Pedro (MATRIZes, 2023)
This text seeks to synthesize the relationship with the Post-Graduation Program in Communication Sciences of the Universidade de São Paulo, established by the work with professors Clotilde Pérez and Eneus Trindade, more than fifteen years ago, when moved by mutual research curiosity , due to the shared certainty about the need to expand the field of study of the advertising discipline, a professional and human relationship was born, one that has grown during all these years, in which our way of understanding and approaching the advertising phenomenon has been consolidated as interdisciplinary, exploratory and collaborative, thus generating ideas that transcend the study of the advertising phenomenon to encompass the consumer culture.